2023
DOI: 10.3390/cancers15123182
|View full text |Cite
|
Sign up to set email alerts
|

Could Oxidative Stress Play a Role in the Development and Clinical Management of Differentiated Thyroid Cancer?

Abstract: Increased oxidative stress (OS) has been implicated as a relevant risk factor for cancer progression. Furthermore, patients diagnosed with differentiated thyroid cancer (DTC) have been characterized by an increased OS status. Therefore, assessing OS status could potentially be considered a useful tool in DTC clinical management. This measurement could be particularly valuable in personalizing treatment protocols and determining new potential medical targets to improve commonly used therapies. A literature revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 126 publications
0
9
0
Order By: Relevance
“…6 The future of antioxidant treatment discussion: considerations and opportunities for metformin intervention Since oxidative stress is involved in the pathogenesis of many diseases, it is crucial to find ways to overcome its negative impact (Blacker and Duchen, 2016;Buczyńska et al, 2021a;Adamska et al, 2021;Buczyńska et al, 2021b;Buczyńska et al, 2023a;Buczyńska et al, 2023b;Buczyńska et al, 2023c;Kościuszko et al, 2023). This review focused on presenting new and promising mechanisms responsible for the potential antioxidant use of metformin, while forecasting further research directions (Salvatore et al, 2021).…”
Section: Metformin As An Antioxidant In Clinical Trials: Advancement ...mentioning
confidence: 99%
“…6 The future of antioxidant treatment discussion: considerations and opportunities for metformin intervention Since oxidative stress is involved in the pathogenesis of many diseases, it is crucial to find ways to overcome its negative impact (Blacker and Duchen, 2016;Buczyńska et al, 2021a;Adamska et al, 2021;Buczyńska et al, 2021b;Buczyńska et al, 2023a;Buczyńska et al, 2023b;Buczyńska et al, 2023c;Kościuszko et al, 2023). This review focused on presenting new and promising mechanisms responsible for the potential antioxidant use of metformin, while forecasting further research directions (Salvatore et al, 2021).…”
Section: Metformin As An Antioxidant In Clinical Trials: Advancement ...mentioning
confidence: 99%
“…Nearly a century ago, Warburg observed that cancer cells can convert glucose into lactate even when oxygen is available, a phenomenon termed aerobic glycolysis or the “Warburg effect” ( Liberti et al, 2016 ). Subsequent research has demonstrated increased expression of glucose transporters (GLUTs) alongside decreased oxidative metabolism in cancer cells ( Tran et al, 2016 ; Kościuszko et al, 2023 ). While the Warburg hypothesis is well-established, the precise adaptive mechanisms responsible for reduced oxidative metabolism in cancer cells remain unclear in many carcinoma models ( Schiliro et al, 2021 ).…”
Section: Warburg Effect–the Novel Target In Ptc Clinical Managementmentioning
confidence: 99%
“…For instance, the 2 -oxidized form of guanine, 8-oxo-deoxyguanosine, is a valuable marker of oxidative DNA damage during carcinogenesis, and its prognostic significance has been demonstrated in solid tumors, including TC [107,108]. Oxidative stress, defined as an imbalance caused by excessive production of pro-oxidant substances, such as ROS (e.g., superoxide anion, hydroxyl and peroxyl radicals, hydrogen peroxide-H 2 O 2 ) and reactive nitrogen species (RNS, e.g., peroxynitrite, nitrosoperoxycarbonate), and/or by inefficient functioning of antioxidant systems [15], has been recently linked to TC development and progression [105,109,110]. ROS are mainly produced at sites on the mitochondrial complexes I and III of the electron transport chain, as a byproduct of respiration, and also through a number of enzymatic systems, including nicotinamide adenine dinucleotide phosphate oxidases (NOXs), xanthine oxidases, nitric oxide (NO) synthase, and cytochrome P450 reductase [103,105].…”
Section: Oxidative Stress In Thyroid Cancermentioning
confidence: 99%
“…ROS are mainly produced at sites on the mitochondrial complexes I and III of the electron transport chain, as a byproduct of respiration, and also through a number of enzymatic systems, including nicotinamide adenine dinucleotide phosphate oxidases (NOXs), xanthine oxidases, nitric oxide (NO) synthase, and cytochrome P450 reductase [103,105]. Thyroid cells are thought to have a relatively high tolerance to oxidative stress compared to many other cell types [110], due to the involvement of ROS in the initial stages of thyroid hormone synthesis during dietary iodide oxidation by TPO-and H 2 O 2 -generating enzymes, the dual oxidases (DUOXs) 1 and 2 [15,111]. Both DUOX1 and -2, members of the NOX family, are expressed in the thyroid, though the expression level of DUOX2 is fivefold higher compared to DUOX1, and the role of the latter in the gland remains largely unknown [112,113].…”
Section: Oxidative Stress In Thyroid Cancermentioning
confidence: 99%